2020
DOI: 10.3390/foods9070902
|View full text |Cite
|
Sign up to set email alerts
|

Physiochemical Characteristics of Hot and Cold Brew Coffee Chemistry: The Effects of Roast Level and Brewing Temperature on Compound Extraction

Abstract: The role of roasting in cold brew coffee chemistry is poorly understood. The brewing temperature influences extraction processes and may have varying effects across the roast spectrum. To understand the relationship between brew temperature and roast temperature, hot and cold brew coffees were prepared from Arabica Columbian coffee beans roasted to light, medium, and dark levels. Chemical and physical parameters were measured to investigate the relationships among degree of roast, water temperature, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 58 publications
9
63
1
4
Order By: Relevance
“…This supports the results of the ranking test, in which cold brew was preferred over hot brewed coffee. Our results also corroborate previous literature about considerable taste differences between hot and cold brews [ 28 ], which may be caused by differential extraction of key characteristic compounds such as acids [ 29 ] and several volatile compounds [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…This supports the results of the ranking test, in which cold brew was preferred over hot brewed coffee. Our results also corroborate previous literature about considerable taste differences between hot and cold brews [ 28 ], which may be caused by differential extraction of key characteristic compounds such as acids [ 29 ] and several volatile compounds [ 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…It may be related to the higher content of caffeoylquinic and chlorogenic acid isomers in hot-brewed coffee than in cold-brewed infusions. Rao et al [ 28 ] also suggested that hot water can more easily wet the oily surface of coffee beans, to enhance the efficiency of extraction of active compounds, including those with antioxidant potential. Coffee brewing using hot or cold water could affect the different solubilities of compounds with higher molecular weight, mainly melanoidins.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the extraction from the surface and near-surface matrix occurs more rapidly than the diffusion of compounds through the intragranular pore network to the grain surface. In another study, Rao et al [ 28 ] compared, among others, the content of bioactive compounds in infusions prepared using cold and hot methods, from coffee beans with varying roasting degrees. They found that the roasting process led to several chemical and physical changes in the bean matrix.…”
Section: Resultsmentioning
confidence: 99%
“…In the last years, consumers have shown great interest in “cold brew”, a coffee beverage prepared with cold water (room temperature or refrigerated water) for up to 24 h [ 32 ]. Recent studies indicate that hot and cold brew coffees have small but important differences, particularly in the total antioxidant capacity of the resulting coffee [ 21 ]. Although melanoidins have not been characterized in cold brew coffee ( Table 1 ) [ 33 ], water extraction temperature causes differential solubility of these molecules [ 34 ].…”
Section: Introductionmentioning
confidence: 99%